Preparation method for synthesizing montmorillonite-based composite microwave absorbing material by one-pot method and montmorillonite-based composite microwave absorbing material prepared by the method

Synthesis of montmorillonite-based composite absorbing materials by one-pot method has solved the problem that the preparation of composite absorbing materials in the prior art is difficult to be large-scale, low-cost and batch, and the efficient preparation and performance optimization of montmorillonite-based composite absorbing materials are achieved.

CN116284770BActive Publication Date: 2025-04-25WEI SHIMIN (XIAMEN) INTELLIGENT TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310213628.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-07
Publication Date
2025-04-25
Estimated Expiration
2043-03-07

AI Technical Summary

Technical Problem

The existing methods of composite absorbing materials are difficult to achieve large-scale, low-cost, and batch preparation, and cannot effectively solve the harm of electromagnetic radiation to equipment and biological health.

Method used

The preparation method of synthesizing montmorillonite-based composite absorbing material by one-pot method is used to synthesize montmorillonite and iron salt in deionized water, sonication and mechanical stirring, alkali solution and a mixture of pyrrole or pyrrole and aniline are added to initiate polymerization, and polypyrrole composite montmorillonite-based ferrite is obtained.

Benefits of technology

It realizes the large-scale industrial synthesis and preparation of montmorillonite-based composite wave absorbing materials with simple operation, low cost and excellent performance, with excellent dielectric loss and magnetic loss performance, and controllable performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116284770B_ABST
    Figure CN116284770B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electromagnetic wave absorbing materials, and in particular to a preparation method for synthesizing a montmorillonite-based composite wave absorbing material in one pot and a montmorillonite-based composite wave absorbing material prepared by the method. The preparation method comprises dispersing montmorillonite and iron salt in deionized water, and obtaining a uniform mixed solution by ultrasonic treatment and mechanical stirring; adding an alkaline solution to the mixed solution, heating it to 50-110° C., and reacting under stirring to obtain a montmorillonite-based ferrite solution; adding pyrrole or a mixture of pyrrole and aniline to the montmorillonite-based ferrite solution at room temperature, and then adding peroxide to initiate polymerization of pyrrole or a mixture of pyrrole and aniline to obtain a polypyrrole composite montmorillonite-based ferrite, and drying after washing to obtain a montmorillonite-based composite wave absorbing material. The method is simple to operate, low in cost, and excellent in performance, and can be prepared by industrial synthesis in large quantities. And the wave absorbing material obtained by the method has excellent dielectric loss and magnetic loss properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electromagnetic wave absorbing materials, and in particular to a method for preparing a montmorillonite-based composite wave absorbing material by a one-pot method and the montmorillonite-based composite wave absorbing material prepared by the method. Background Art

[0002] Electromagnetic radiation caused by electromagnetic waves not only endangers the normal operation of equipment, but also causes certain harm to biological health. A single type of absorbing material is affected by itself and it is difficult to achieve a relatively ideal absorbing effect. In order to achieve a relatively ideal absorbing effect, magnetic absorbing materials are generally compounded with dielectric and resistive absorbing materials to obtain composite absorbing materials with a relatively ideal absorbing effect.

[0003] For example, the polymethacrylimide composite foam absorbing material disclosed in the patent document with the announcement number CN103923337B is prepared by the following steps: (1) surface treatment of the absorber: the absorber, the surface treatment agent and the solvent are mixed evenly, and then ultrasonically treated, the solvent is removed by drying, and then crushed and ground to obtain the surface-treated absorber; (2) preparation of expandable polymethacrylimide resin particles; (3) preparation of the polymethacrylimide composite foam absorbing material.

[0004] Another example is a method for preparing an electromagnetic absorbing layer of an electric meter box based on flower-shaped carbonyl iron particles disclosed in a patent document with publication number CN105924618A. First, an appropriate amount of reactants is taken, and the reactants include a reducing agent, an iron salt, a stabilizer, a chelating agent and a pH regulator; then the reducing agent and the pH regulator are dissolved in deionized water and a reducing agent mixed solution is formed under magnetic stirring; the iron salt, the stabilizer and the chelating agent are added to the deionized water and stirred to form an iron salt mixed solution; the reducing agent mixed solution and the iron salt mixed solution are dripped into a chemical plating reaction tank for sufficient reaction; finally, the reaction product is collected with a magnet and washed and dried to obtain iron nanowire particles.

[0005] At present, the preparation methods of composite absorbing materials include arc plasma method, hydrothermal method, solvothermal method and other methods. These methods are often difficult to achieve large-scale, low-cost, and batch preparation. Summary of the invention

[0006] In order to solve the problem that the preparation method of the composite absorbing material in the prior art cannot be prepared in large quantities, the present invention provides a one-pot method for synthesizing a montmorillonite-based composite absorbing material, comprising the following preparation steps:

[0007] The montmorillonite and the iron salt are dispersed in deionized water, and a uniform mixed solution is obtained by ultrasonic treatment and mechanical stirring;

[0008] Adding an alkaline solution to the mixed solution, heating it to 50-110° C., and reacting under stirring to obtain a montmorillonite-based ferrite solution;

[0009] Adding pyrrole or a mixture of pyrrole and aniline to the montmorillonite-based ferrite solution at room temperature, and then adding peroxide to initiate polymerization of pyrrole or the mixture of pyrrole and aniline to obtain a polypyrrole composite montmorillonite-based ferrite, and then washing and drying to obtain the montmorillonite-based composite absorbing material;

[0010] The iron salt is at least one of ferrous sulfate, ferric sulfate, ferrous nitrate, ferric nitrate, ferrous chloride, ferric chloride, and ferric acetate, but is not limited thereto;

[0011] The mixing volume ratio of the pyrrole and the aniline is 1:10 to 10:1.

[0012] In one embodiment, the mass ratio of the montmorillonite, the iron salt, the deionized water and the peroxide is 1-5:2-10:100-120:0.5-2.0.

[0013] In one embodiment, the volume ratio of the alkaline solution, pyrrole or the mixture of pyrrole and aniline to the deionized water is 5-10:5-20:100-120.

[0014] In one embodiment, the montmorillonite is at least one of sodium-based montmorillonite, magnesium-based montmorillonite, sodium-calcium-based montmorillonite, and calcium-based montmorillonite.

[0015] In one embodiment, the iron salt is preferably ferrous sulfate.

[0016] In one embodiment, the alkaline solution is at least one of 28% to 30% by mass ammonia water, 3% to 30% by mass sodium hydroxide solution, and 3% to 30% by mass potassium hydroxide solution, but is not limited thereto, among which ammonia water solution is preferred.

[0017] In one embodiment, the peroxide is at least one of ammonium persulfate, potassium persulfate, methyl ethyl ketone peroxide, and azobisisobutyronitrile, but is not limited thereto, among which ammonium persulfate is preferred.

[0018] In one embodiment, the washing is performed by sequentially washing with deionized water and ethanol at least three times.

[0019] The present invention also provides a montmorillonite-based composite wave absorbing material, which is prepared by any one of the above-mentioned one-pot synthesis methods for preparing the montmorillonite-based composite wave absorbing material.

[0020] Based on the above, compared with the prior art, the present invention has the following technical effects:

[0021] The one-pot method for preparing a montmorillonite-based composite wave-absorbing material provided by the present invention has the advantages of simple operation, low cost, excellent performance, and can be prepared by industrial synthesis in large quantities.

[0022] The montmorillonite-based composite wave absorbing material provided by the present invention uses montmorillonite as a template, loads a layer of magnetic ferroferric oxide on the surface of the montmorillonite, and then loads a layer of polypyrrole, thereby realizing the organic composite of magnetic wave absorbing material and resistive wave absorbing material. The composite wave absorbing material has excellent dielectric loss and magnetic loss performance, and the dielectric loss or magnetic loss parameters can be adjusted by adjusting the ratio of iron salt and polypyrrole, thereby realizing the controllable performance of the material.

[0023] Other features and beneficial effects of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other beneficial effects of the present invention can be realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. The positional relationships described in the drawings in the following description are based on the directions in which the components are drawn in the diagrams, unless otherwise specified.

[0025] Figure 1 TEM and element distribution diagram of the montmorillonite-based composite absorbing material prepared in Example 1. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] In the description of the present invention, it should be noted that all terms (including technical terms and scientific terms) used in the present invention have the same meanings as those generally understood by ordinary technicians in the field to which the present invention belongs, and should not be understood as limitations on the present invention; it should be further understood that the terms used in the present invention should be understood to have the same meanings as these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in this invention.

[0028] The present invention provides a one-pot method for preparing a montmorillonite-based composite absorbing material, and the specific operations are as follows:

[0029] Disperse 1 to 5 parts by weight of montmorillonite and 2 to 10 parts by weight of iron salt in 100 to 120 parts by weight of deionized water, perform ultrasonic treatment for 5 to 90 minutes, and mechanically stir for 5 to 90 minutes to obtain a uniform mixed solution;

[0030] Add 5 to 10 parts by volume of an alkaline solution to the mixed solution, raise the temperature to 50 to 110° C., and mechanically stir at 200 to 1000 r / min for 0.5 to 4 hours to obtain a montmorillonite-based ferrite solution;

[0031] At room temperature, 5 to 20 parts by volume of pyrrole or a mixture of pyrrole and aniline are added to the above montmorillonite-based ferrite solution, and then 0.5 to 2.0 parts by weight of peroxide are added to initiate polymerization of pyrrole or pyrrole and aniline for 2 to 24 hours to obtain a polypyrrole composite montmorillonite-based ferrite, and the solution is washed with deionized water and ethanol for more than 3 times, and then dried to obtain the montmorillonite-based composite absorbing material.

[0032] The present invention provides the following embodiments

[0033] Example 1

[0034] 5 g of montmorillonite and 10 g of FeSO4·7H2O were dispersed in 120 ml of deionized water, ultrasonically treated for 30 min, and mechanically stirred for 20 min to obtain a uniform mixed solution.

[0035] Add 7 ml of 28% to 30% ammonia water to the mixed solution, heat the mixture to 80°C in an oil bath, and mechanically stir at 500 r / min for 2 hours to obtain a montmorillonite-based ferrite solution.

[0036] At room temperature, 10 ml of pyrrole was added to the above montmorillonite-based ferrite solution, and then 1.0 g of ammonium persulfate was added to initiate pyrrole polymerization for 12 h to obtain a polypyrrole composite montmorillonite-based ferrite, which was then washed with deionized water and ethanol for 3 times and then dried to obtain a montmorillonite-based composite absorbing material. Figure 1 TEM and element distribution diagram of the material.

[0037] Example 2

[0038] 5 g of montmorillonite and 10 g of FeCl3 were dispersed in 120 ml of deionized water, ultrasonically treated for 30 min, and mechanically stirred for 20 min to obtain a uniform mixed solution;

[0039] Add 7 ml of 10% wt sodium hydroxide to the above mixed solution, place in an oil bath at 80°C, and mechanically stir at 300 r / min for 2 hours to obtain a montmorillonite-based ferrite solution;

[0040] At room temperature, 5 ml of pyrrole and 5 ml of aniline were added to the above montmorillonite-based ferrite solution, and then 1.0 g of ammonium persulfate was added to initiate pyrrole polymerization for 12 hours to obtain a polypyrrole composite montmorillonite-based ferrite, which was washed with deionized water and ethanol for more than 3 times and then dried to obtain a montmorillonite-based composite absorbing material.

[0041] Example 3

[0042] 5 g of montmorillonite and 10 g of Fe(NO3)2·6H2O were dispersed in 120 ml of deionized water, ultrasonicated for 30 min, and mechanically stirred for 20 min to obtain a uniform mixed solution;

[0043] Add 7 ml of 10% wt sodium hydroxide to the above mixed solution, place in an oil bath at 80°C, and mechanically stir at 500 r / min for 2 hours to obtain a montmorillonite-based ferrite solution;

[0044] At room temperature, 9 ml of pyrrole and 1 ml of aniline were added to the above solution, and then 1.0 g of ammonium persulfate was added to initiate pyrrole polymerization for 12 hours to obtain a polypyrrole composite montmorillonite-based ferrite, which was washed with deionized water and ethanol for 3 times and then dried to obtain a montmorillonite-based composite absorbing material.

[0045] Example 4

[0046] 5 g of montmorillonite and 10 g of ferric acetate were dispersed in 120 ml of deionized water, ultrasonically treated for 30 min, and mechanically stirred for 20 min to obtain a uniform mixed solution.

[0047] Add 7 ml of 28% to 30% ammonia water to the mixed solution, heat the mixture to 80°C in an oil bath, and mechanically stir at 500 r / min for 2 hours to obtain a montmorillonite-based ferrite solution.

[0048] 10 ml of pyrrole was added to the above montmorillonite-based ferrite solution at room temperature, and then 1.0 g of ammonium persulfate was added to initiate pyrrole polymerization for 12 hours to obtain a polypyrrole composite montmorillonite-based ferrite, which was washed with deionized water and ethanol for 3 times and then dried to obtain a montmorillonite-based composite absorbing material.

[0049] Example 5

[0050] 5 g of montmorillonite and 10 g of FeSO4·7H2O were dispersed in 120 ml of deionized water, ultrasonically treated for 30 min, and mechanically stirred for 20 min to obtain a uniform mixed solution.

[0051] Add 7 ml of 10% potassium hydroxide to the mixed solution, heat the mixture to 80°C in an oil bath, and mechanically stir at 500 r / min for 2 hours to obtain a montmorillonite-based ferrite solution.

[0052] 10 ml of pyrrole was added to the above montmorillonite-based ferrite solution at room temperature, and then 1.0 g of ammonium persulfate was added to initiate pyrrole polymerization for 12 hours to obtain a polypyrrole composite montmorillonite-based ferrite, which was washed with deionized water and ethanol for 3 times and then dried to obtain a montmorillonite-based composite absorbing material.

[0053] Example 6

[0054] 5 g of montmorillonite and 10 g of FeSO4·7H2O were dispersed in 120 ml of deionized water, ultrasonically treated for 30 min, and mechanically stirred for 20 min to obtain a uniform mixed solution.

[0055] Add 7 ml of 28% to 30% ammonia water to the mixed solution, heat the mixture to 80°C in an oil bath, and mechanically stir at 500 r / min for 2 hours to obtain a montmorillonite-based ferrite solution.

[0056] 10 ml of pyrrole was added to the above montmorillonite-based ferrite solution at room temperature, and then 1.0 g of potassium persulfate was added to initiate pyrrole polymerization for 12 hours to obtain a polypyrrole composite montmorillonite-based ferrite, which was washed with deionized water and ethanol for 3 times and then dried to obtain a montmorillonite-based composite absorbing material.

[0057] The present invention also provides the following comparative example

[0058] Comparative Example 1

[0059] It comes from commercially available ferroferric oxide, where the fineness of the ferroferric oxide is 200nm~2μm, and it is prepared into a paraffin sample with a mass fraction of ferroferric oxide of 70% for testing.

[0060] Comparative Example 2

[0061] 5 g of halloysite and 10 g of FeSO4·7H2O were dispersed in 120 ml of deionized water, ultrasonically treated for 30 min, and mechanically stirred for 20 min to obtain a uniform mixed solution.

[0062] Add 7 ml of 28% to 30% ammonia water to the mixed solution, heat the mixture to 80°C in an oil bath, and mechanically stir at 500 r / min for 2 hours to obtain a halloysite-based ferrite solution.

[0063] 10 ml of pyrrole was added to the above montmorillonite-based ferrite solution at room temperature, and then 1.0 g of potassium persulfate was added to initiate pyrrole polymerization for 12 hours to obtain a polypyrrole composite montmorillonite-based ferrite, which was washed with deionized water and ethanol for 3 times and then dried to obtain a halloysite-based composite absorbing material.

[0064] Comparative Example 3

[0065] 5 g of montmorillonite and 10 g of CoSO4·7H2O were dispersed in 120 ml of deionized water, ultrasonically treated for 30 min, and mechanically stirred for 20 min to obtain a uniform mixed solution.

[0066] Add 7 ml of 28% to 30% ammonia water to the mixed solution, heat the mixture to 80°C in an oil bath, and mechanically stir at 500 r / min for 2 hours to obtain a montmorillonite-based cobalt oxide solution.

[0067] At room temperature, 10 ml of pyrrole was added to the above montmorillonite-based cobalt oxide solution, and then 1.0 g of potassium persulfate was added to initiate pyrrole polymerization for 12 hours to obtain a polypyrrole composite montmorillonite-based cobalt oxide, which was washed with deionized water and ethanol for 3 times and then dried to obtain a montmorillonite-based cobalt oxide composite absorbing material.

[0068] The absorbing materials prepared in the above embodiments and comparative examples were tested for 2-18 GHz electromagnetic parameters according to GJB 5239-2004 RF absorbing material absorbing performance test method (coaxial method). The test results are shown in Table 1 and Table 2:

[0069] Table 1 - Example sample absorption parameters

[0070]

[0071] Table 2 - Absorption parameters of comparative samples

[0072]

[0073] It can be seen from the test results of Table 1 and Table 2 that the absorbing properties of the absorbing materials prepared by the preparation method provided by the present invention are better than those of the samples in the comparative examples. It can be seen from comparative example 1 that the absorbing material prepared by the present invention is significantly better than the ferroferric oxide absorbing material commonly used in the art in terms of performance. Comparative example 2 uses halloysite instead of the montmorillonite of the present invention, and comparative example 3 uses conventional cobalt salt instead of the iron salt of the present invention, but both fail to achieve the same absorbing effect, indicating that the iron salt loaded on montmorillonite of the present invention can better improve the absorbing performance.

[0074] In addition, it can be seen from Table 1 that the wave absorbing performance of Example 1 is better than that of other comparative examples, indicating that the iron salt of the present invention uses ferrous sulfate, the alkaline solution uses an ammonia solution, and the peroxide uses ammonium persulfate, which can further improve the performance of the wave absorbing ability prepared therein.

[0075] In summary, compared with the prior art, the absorbing material provided by the present invention has excellent dielectric loss and magnetic loss performance. By adjusting the ratio of iron salt and polypyrrole, the dielectric loss or magnetic loss parameters can be adjusted respectively, thereby achieving controllable material performance.

[0076] In addition, those skilled in the art should understand that, although there are many problems in the prior art, each embodiment or technical solution of the present invention can be improved in only one or several aspects, without having to solve all the technical problems listed in the prior art or background technology at the same time. Those skilled in the art should understand that the content not mentioned in a claim should not be used as a limitation on the claim.

[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A one-pot method for preparing a montmorillonite-based composite absorbing material, characterized in that: The method comprises the following preparation steps: The montmorillonite and the iron salt are dispersed in deionized water, and a uniform mixed solution is obtained by ultrasonic treatment and mechanical stirring; Adding an alkaline solution to the mixed solution, heating it to 50-110° C., and reacting under stirring to obtain a montmorillonite-based ferrite solution; Adding pyrrole or a mixture of pyrrole and aniline to the montmorillonite-based ferrite solution at room temperature, and then adding peroxide to initiate polymerization of pyrrole or the mixture of pyrrole and aniline to obtain a polypyrrole composite montmorillonite-based ferrite, and then washing and drying to obtain the montmorillonite-based composite absorbing material; The iron salt is at least one of ferrous sulfate, ferric sulfate, ferrous nitrate, ferric nitrate, ferrous chloride, ferric chloride, and ferric acetate; The mixing volume ratio of the pyrrole and the aniline is 1:10 to 10:

1.

2. The method for preparing a one-pot synthesis of montmorillonite-based composite absorbing material according to claim 1, characterized in that: The mass ratio of the montmorillonite, the iron salt, the deionized water and the peroxide is 1-5:2-10:100-120:0.5-2.

0.

3. The method for preparing a one-pot synthesis of montmorillonite-based composite absorbing material according to claim 1, characterized in that: The volume ratio of the alkaline solution, pyrrole or the mixture of pyrrole and aniline to the deionized water is 5-10:5-20:100-120.

4. The method for preparing a one-pot synthesis of montmorillonite-based composite absorbing material according to claim 1, characterized in that: The montmorillonite is at least one of sodium-based montmorillonite, magnesium-based montmorillonite, sodium-calcium-based montmorillonite, and calcium-based montmorillonite.

5. The method for preparing a one-pot synthesis of montmorillonite-based composite absorbing material according to claim 1, characterized in that: The alkaline solution is at least one of 28% to 30% by mass ammonia water, 3% to 30% by mass sodium hydroxide solution, and 3% to 30% by mass potassium hydroxide solution.

6. The method for preparing a one-pot synthesis of montmorillonite-based composite absorbing material according to claim 1, characterized in that: The peroxide is at least one of ammonium persulfate, potassium persulfate, methyl ethyl ketone peroxide, and azobisisobutyronitrile.

7. The method for preparing a one-pot synthesis of montmorillonite-based composite absorbing material according to claim 1, characterized in that: The washing is performed by sequentially washing with deionized water and ethanol for at least 3 times.

8. A montmorillonite-based composite absorbing material, characterized in that: The material is prepared by the one-pot method for synthesizing montmorillonite-based composite microwave absorbing materials as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Polymethacrylimide composite foam microwave absorbing material

    CN103923337B

  • Electric-meter-box electromagnetic wave absorbing layer based on flower-shaped carbonyl iron particles and preparing method

    CN105924618A

  • Hollow multilayer core-shell material with electromagnetic wave adsorption characteristic and preparation method thereof

    CN102504758A

  • Porous microspheres / ferrite / conductive layer composite material used for microwave absorption

    CN110002458A

  • Polyphenylamine composition with clay ore as carrier and its preparing process

    CN1381530A